2020
DOI: 10.1002/jts.22589
|View full text |Cite
|
Sign up to set email alerts
|

Training During a Pandemic: Successes, Challenges, and Practical Guidance From a Virtual Facilitated Learning Collaborative Training Program for Written Exposure Therapy

Abstract: In response to COVID-19, continued workforce training is essential to ensure that evidence-based treatments are available on the frontline to meet communities' ongoing and emerging mental health needs. However, training during a pandemic imposes many new challenges. This paper describes a multisite training and implementation pilot program, facets of which allowed for continued training despite the onset of the COVID-19 pandemic and subsequent social distancing guidelines. This virtual facilitated learning col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Another key mechanism might be how individuals incorporate their experiences into a his/her narrative identity, which is defined as an individual's internalized life story (Infurna and Jayawickreme, 2019 ). The recent high resonance of narrative-based therapies in trauma research may give this hypothesis a further boost (Lely et al, 2019 ; Worley et al, 2020 ). Furthermore, a narrative-based resilience mechanism may represent a link to an interdisciplinary approach of social sciences with the humanities, an area that deserves more attention in light of the call for more interdisciplinary work (Richter, 2017 ; Lindert et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another key mechanism might be how individuals incorporate their experiences into a his/her narrative identity, which is defined as an individual's internalized life story (Infurna and Jayawickreme, 2019 ). The recent high resonance of narrative-based therapies in trauma research may give this hypothesis a further boost (Lely et al, 2019 ; Worley et al, 2020 ). Furthermore, a narrative-based resilience mechanism may represent a link to an interdisciplinary approach of social sciences with the humanities, an area that deserves more attention in light of the call for more interdisciplinary work (Richter, 2017 ; Lindert et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that PTSD treatments delivered via TMH are acceptable, effective, and noninferior to in-person treatment delivery (see Morland et al, 2020 for a review); however, comparisons of delivery modality have not yet been reported for WET. Data about WET’s effectiveness via TMH is particularly important because the COVID-19 pandemic has forced much of VA service to shift from in-person care to TMH (Rosen et al, 2020; Worley et al, 2020).…”
mentioning
confidence: 99%
“…Based on these pilot trials, specific protocols could be developed to train practitioners and professionals to better handle future crisis. Encouraging evidence from recent multisite training and implementation of pilot programs during the pandemic support such directions (see, for example, Worley et al, 2020 ). Furthermore, given that video and virtual formats have been shown to be effective similarly to in-person care (e.g., Morland et al, 2017 ), this may be another flexible route for adapted therapists training during the current crisis.…”
Section: Discussionmentioning
confidence: 99%